Pelatihan Jurnalistik sebagai Model Komunikasi Kebutuhan Bingkai Kerja Perspektif yang Beragam pada Persepsi “Toko Rotte:” Periklanan dan Hubungan Sponsor Pemasaran Bisnis - Hefri Yodiansyah; Debby Kurniadi; Hari Jaumaulana (AMMA : Jurnal Pengabdian Masyarakat, 2022)
Objective Lens—This paper describes the conceptual framework of journalistic training for “Rotte store” relational marketing governance. Implementation Method- The store governance framework develops the features of advertising and marketing promotion by first identifying the main factor analysis, the determinants of the perceived social needs of the community, and the main tool features of the benefits process and journalistic methods for making rational decisions. Results Findings-The resulting theoretical paradigm visualizes that the existence of entrepreneurship affects efforts to increase users as an institutional, economic, social & cultural industry. Conclusion-The level of income of store shoppers and consumers, and the governance process with marketing promotions, especially those operating at the level of contextual theory, while influencing marketing governance through rational consumer attitudes differ in more detail and proximal to the dominant product and develop marketing promotions for providing valuable social environmental insight into knowledge managing diverse perspectives, related to the complex needs generated perception of their promotions perception analysis of meaningful components of the marketing communication mix paradigm method of human needs on the promotion of their consumer perceptions.